Tourist Perceptions Toward Tourism Attraction In Ramban Biak Tourism Village Of Lenek, East Lombok - Muh. Nuh Ilyas; Taufiq Kurniawan; Ahmad Ahmad (Universitas Katolik Widya Karya Malang, 2023)
This research journal reviews tourists' perceptions of tourist attractions in Lenek Ramban Biak Village. This research is a type of descriptive qualitative research. The population in this study were tourists visiting Lenek Ramban Biak Village. Samples were taken from tourists who visited as many as 100 respondents with incidental sampling technique. Data was collected using a questionnaire and analyzed using descriptive analysis techniques. The results showed that tourists' perceptions of the tourist attractions of Lenek Ramban Biak in terms of the dimensions of attractions and accessibility with agreed criteria. That means that the tourist attraction of Lenek Ramban Biak Village has unique nature, traditions and culture. There is a Camping place, a friendly community. While on the dimensions of the amenities with the criteria quite agree.